CONTINUITY AND CHANGE IN SUNDANESE PANANYAAN: Contesting an Islamicate Tradition in West Java (JOURNAL OF INDONESIAN ISLAM, 2018)
This paper aims to discuss the development of pananyaan, a name for Sundanese-Priangan local shaman in terms of continuity and change. Using ethnographical method, it will provide an anthropological account of these elderly people through the investigation of the major shifts of them and their meanings, to the grand narration of Islamization process. The exploration based on the research questions leads to several conclusions. The existence of pananyaan has become primordial nature of the belief toward supernatural being. There are, at least, several major shifts in the origins pananyaan to the present. First, the shift of domestic spiritualism from local spirit to Islamic saints that reflected an elementary form of the intersection of Islam and local customs. Second, the emergence of ahli hikmah, that reflected such an outward appearance in the intersection as represented by several hybrid incantations and supernatural powers. Third, the contemporary shaman, whose Islam and local customs are united in one fashion with the influence of modern determinations. In addition, the still-taking place Islamization has become a challenge for the next development of pananyaan.